2017
DOI: 10.1038/s41467-017-00257-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and HLA region fine-mapping studies identify susceptibility loci for multiple common infections

Abstract: Infectious diseases have a profound impact on our health and many studies suggest that host genetics play a major role in the pathogenesis of most of them. We perform 23 genome-wide association studies for common infections and infection-associated procedures, including chickenpox, shingles, cold sores, mononucleosis, mumps, hepatitis B, plantar warts, positive tuberculosis test results, strep throat, scarlet fever, pneumonia, bacterial meningitis, yeast infections, urinary tract infections, tonsillectomy, chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
222
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(240 citation statements)
references
References 77 publications
15
222
2
1
Order By: Relevance
“…We have also identified a number of associations which were suggestive but not genome-wide significant Supplementary Table S2). It is noteworthy to mention that some of those have been found to be associated with other types of infections, even significantly so, in an aforementioned study (Tian et al 2017). For example, rs687621 (P = 4.94 × 10 -6 in our study) was genome-wide significantly associated with childhood ear infections.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We have also identified a number of associations which were suggestive but not genome-wide significant Supplementary Table S2). It is noteworthy to mention that some of those have been found to be associated with other types of infections, even significantly so, in an aforementioned study (Tian et al 2017). For example, rs687621 (P = 4.94 × 10 -6 in our study) was genome-wide significantly associated with childhood ear infections.…”
Section: Discussionsupporting
confidence: 49%
“…However, even if the effect of the SNP on the phenotype is through an immune mechanism captured by one of the above markers, it might still not be necessarily appropriate to correct for the latter to assess the total causal effect (Schisterman et al 2009). Our top SNP was also highlighted in a study of different kinds of infections, although it was only associated with tonsillectomy at a genome-wide level of significance (Tian et al 2017). Interestingly, it lies close to the ABO gene and was reported as an expression quantitative trait locus (eQTL) for the gene in whole blood (P = 3.6 × 10 -34 ), GTEx Browser, accessed on October 2nd 1 3 2019 (GTEx Consortium 2013), which is of particular interest, since connections between blood groups and infections have been observed previously, and the expression of blood groups is connected to the maturation of the gastrointestinal microbiome (Cooling 2015).…”
Section: Discussionmentioning
confidence: 78%
“…This study further demonstrated that the associated variants are correlated with the methylation status (cg05678571, p = 1.43 × 10 −6 ) and expression levels (p = 9.3 × 10 −5 ) of the FNDC1 gene. Also, an independent GWAS study on more than 200,000 individuals of European ancestry reported 14 genomic regions, including FUT2 (p-value: 3.51 × 10 −30 ), TBX1 (1.17 × 10 −19 ), HLA-DRB1 (rs4329147, 9.55 × 10 −12 ), ABO (3.67 × 10 −11 ), EFEMP1 (1.47 × 10 −10 ), AUTS2 (3.75 × 10 −9 ), CDHR3 (5.40 × 10 −9 ), BSN (1.56 × 10 −8 ), and PLG (3.78 × 10 −8 ), that were significantly associated with childhood ear infection (Tian et al, 2017), further highlighting the contribution of genetic factors responsible for OM in humans.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…[13,20,27]. Обнаружены популяционные и этнические особенности ассоциаций комплекса HLA с различными инфекционными заболеваниями, такими как острые респираторно-вирусные инфекции, вирусные гепатиты, а также бактериальные инфекции [10,12,26]. Однако поиск ассоциаций гаплотипов HLA с инфекционными заболеваниями усложнен, так как даже сформированные по признаку национальной принадлежности популяционные группы содержат разнообразный спектр вариантов генов HLA.…”
unclassified